Barley and rye prolamins induce an mRNA interferon‐γ response in coeliac mucosa - BRACKEN, S. C.; KILMARTIN, C.; WIESER, H.; JACKSON, J.; FEIGHERY, C. (Alimentary pharmacology & therapeutics, 2006)
Summary Background In coeliac disease, wheat, barley and rye are traditionally excluded in the gluten‐free diet. However, few studies have examined the small intestinal immune response to barley and rye. Aim To investigate the immunogenicity of barley and rye prolamins (hordein and secalin respectively) in comparison with wheat gliadin. Methods Duodenal biopsies from 22 coeliac patients and 23 disease controls were cultured for 4 h with gliadin, hordein or secalin and compared with culture medium alone. Proinflammatory cytokines, interferon‐γ and interleukin‐2, were quantified by TaqMan polymerase chain reaction and enzyme‐linked immunosorbent assay. Results Hordein caused the greatest increase in interferon‐γ mRNA in coeliac patients (median: 3.3‐fold) in comparison with control subjects (median: 0.28‐fold, P < 0.085). Secalin and gliadin induced similar levels of interferon‐γ mRNA with median fold‐changes of 3.4 and 2.8, respectively, in coeliac patients in comparison with 1.6‐ and 1.1‐fold increases in control subjects (P < 0.294 and P < 0.105, respectively). The median fold‐changes for interleukin‐2 mRNA did not differ between coeliac patients and controls. Cytokine protein was not upregulated. Conclusion The findings of this study provide evidence that barley and rye cause immune activation in the mucosa of coeliac patients and support the practice that barley and rye should be excluded from the gluten‐free diet.